Effect of Utilizing Prosopis Juliflora Ash as Cementitious Material - Amal Anik S, George; Kathirvel, Parthiban; G, Murali (International Journal of Engineering and Technology, 2018)
Since the building made of cement concrete consumes almost half of the total energy generated and accordingly accountable for huge amount of CO2 emission, it is necessary to replace the Portland cement (PC) with sustainable construction material. Similarly, Prosopis julifloraÂ is a shrub or small tree in the family Fabaceae, a kind of mesquite which is considered to be a potential threat for ground water in South India. Hence, this has to eradicate so as to maintain the groundwater and also to effectively utilize its ash thereby reducing environmental pollution, this can be used as a partial replacement for cement. In this regard, this paper investigates the technical feasibility of using prosopis juliflora ash (PJA) as cementitious material by partially (10, 20, 30 and 40 %) replacing cement by prosopis juliflora ash. The mixes were evaluated for their fresh, physical and strength properties such as workability, density and compressive strength and the results were compared with the conventional mix